2023
DOI: 10.3390/met13101638
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Aging Treatment on Microstructure and Performance of Al-Zn-Mg-Cu Alloy Thin Sheets

Peiyue Li,
Minghui Zhang,
Boyang Zhang
et al.

Abstract: Al-Zn-Mg-Cu alloy, recognized for its heat-treatable and super-high strength, is a pivotal material for critical structural components in aviation. Consequently, grasping the intricate relationship between heat treatment processes and the microstructural characteristics and properties of the Al-Zn-Mg-Cu alloy is of paramount practical significance. This study encompasses a spectrum of heat treatment methodologies, delving into the diverse effects of distinct aging treatments on the microstructure and performan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…were performed under conditions of 470 °C/2 h of solution temperature and 120 °C of artificial aging, and, in order to learn more about the formation tendency of the GP zone, which is the nucleation site of the η' phase, the region between 0 and 1 h was enlarged and is shown in Figure 1. The heat treatment conditions used in the calculation were the commonly performed T6 heat treatment conditions for Al-Mg-Zn-Cu-based aluminum alloys [14][15][16]. It was confirmed that the GP zone was formed rapidly at a temperature of 120 °C, peaked within about 30 min of aging, and then transformed to η' and decreased.…”
Section: Alloy and Process Designmentioning
confidence: 92%
See 1 more Smart Citation
“…were performed under conditions of 470 °C/2 h of solution temperature and 120 °C of artificial aging, and, in order to learn more about the formation tendency of the GP zone, which is the nucleation site of the η' phase, the region between 0 and 1 h was enlarged and is shown in Figure 1. The heat treatment conditions used in the calculation were the commonly performed T6 heat treatment conditions for Al-Mg-Zn-Cu-based aluminum alloys [14][15][16]. It was confirmed that the GP zone was formed rapidly at a temperature of 120 °C, peaked within about 30 min of aging, and then transformed to η' and decreased.…”
Section: Alloy and Process Designmentioning
confidence: 92%
“…Therefore, currently, Al-Mg-Si alloys are mainly used, which have high formability and relatively low yield strength, even after natural aging, and excellent bakehardening characteristics after paint bake treatment. On the other hand, in the case of Al-Mg-Zn-Cu alloys, it is generally known that maximum strength is obtained through artificial aging at a temperature of around 120 • C [14][15][16], and excellent mechanical properties of over 500 MPa can be secured [17,18]. But, despite their high-strength characteristics, they are not preferred due to increased yield strength due to natural aging, increased sheet-forming pressure, and reduced mechanical properties due to grain coarsening at bake-hardening temperatures [7,[19][20][21].…”
Section: Introductionmentioning
confidence: 99%